Formulation of Feed with Different Source of Carotenoids on the Colors Quality of Sunkist Balloon Molly Fish (Poecilia sp.) - Nur Fidya Destianti; Himawan Prasetiyo; Ahmad Satibi; Mad Rudi; Ferry Dwi Cahyadi; Agung Setyo Sasongko; Ardana Kurniaji (Department of Aquaculture, 2023)
The parameter value of ornamental fish is determined by the brighter the color of a type of ornamental fish, the higher the value so that farmers need to maintain the color of the ornamental fish by providing feed containing color pigments that can be obtained from vegetable and animal sources of carotenoids. Sunkist balloon molly fish (Poecilia sp.) were stocked in an aquarium measuring 60 × 30 × 30 cm3 (5 fish/l), Objectives of this study was to determine the effect of feeding formulations using different carotenoid sources with the best treatment for improving the color quality of sunkist balloon molly fish (Poecilia sp.). The method used was experimental (quantitative) completely randomized design (CRD) with 3 treatments, 1 control, and 3 repetitions. Feed was given ad libitum (5% body weight) 3 times a day. Color quality data were analyzed using ImageJ Software and one-way ANOVA test. The results of the study showed that feed utilization efficiency, feed conversion ratio and growth performance were not significantly different between treatments. There was a significant effect on improving the quality of the color shown in the P₃ (yellow pumpkin) treatment of 10% as the best treatment among others. Water quality parameter that observed trend to be normal and stable from the beginning to the end of the maintenance period.